2021
DOI: 10.30955/gnj.003249
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue dye in water by using recoverable natural zeolite/Fe3O4 adsorbent

Abstract: <p>In this paper, the low-cost and practical adsorption for removing methylene blue (MB) dye has been developed by using recoverable natural zeolite that was magnetized with Fe3O4. The magnetization was conducted by co-precipitation technique. The adsorbents obtained from the magnetization were characterized by XRD, FTIR, surface area analyzer and turbidity meter machines. The MB adsorption on the recoverable adsorbent was performed by batch experiment. The effect of Fe3O4 fraction on adsorbent character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(51 reference statements)
1
2
0
Order By: Relevance
“… 51,52 Since the MB concentration was maintained constant, for ratios equal or larger than 2, the adsorption uptake percentage was stabilized due to the saturation attributed to the occupation of the active sites and equilibration with the liquid phase. These results were in line to those observed by Wahyuni et al , 19 that reported the impact of the S/L for MB removal from water using recoverable natural zeolite/Fe 3 O 4 adsorbent, showing a yield up to 25 mg/100 mL, but beyond this quantity, no significant increase was observed due to the saturation of the solution that limits interaction with the adsorbent surface.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“… 51,52 Since the MB concentration was maintained constant, for ratios equal or larger than 2, the adsorption uptake percentage was stabilized due to the saturation attributed to the occupation of the active sites and equilibration with the liquid phase. These results were in line to those observed by Wahyuni et al , 19 that reported the impact of the S/L for MB removal from water using recoverable natural zeolite/Fe 3 O 4 adsorbent, showing a yield up to 25 mg/100 mL, but beyond this quantity, no significant increase was observed due to the saturation of the solution that limits interaction with the adsorbent surface.…”
Section: Resultssupporting
confidence: 92%
“…15 Therefore, several authors in their current research have focused on developing methods to protect aquatic environments using adsorbents with a high adsorption capacity. [15][16][17][18][19] Among adsorbents, synthetic and natural zeolites, due to their ability to adsorb drugs, pesticides, pharmaceuticals, metal ions, and dyes have been widely explored. [20][21][22] Andrunik et al 20 tested the potential of y ashbased zeolites and zeolite-carbon composites to remove pesticides from water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation